Dysprosium–dianthracene framework showing thermo-responsive magnetic and luminescence properties. Issue 33 (25th May 2021) - Zou, Qian; Shang, Tao; Huang, Xin-Da; Guo, Qing-Qing; Jia, Jia-Ge; Bao, Song-Song; Zhang, Yi-Quan; Zheng, Li-Min
Abstract : Three-dimensional framework Dy2 (amp2 H2 )2 (C2 O4 )(H2 O)2 ·10H2 O exhibits thermo-induced dehydration and de-dimerization of amp2 H2 2−, accompanied by changes in its single-molecule magnetic behaviour and luminescence properties. Abstract : Metal–organic frameworks showing stimuli-responsive magneto-optical properties are of intensive current interest for potential applications in spintronics and molecular devices. By incorporating a thermo-responsive dianthracene component into a lanthanide phosphonate framework, we successfully obtained compounds Ln2 (amp2 H2 )2 (C2 O4 )(H2 O)2 · x H2 O (MDAF-4Ln, Ln = Dy, x = 10; Gd, x = 9; Er, x = 7; and amp2 H4 = pre-photodimerized 9-anthrylmethylphosphonic acid). These compounds are isostructural showing three-dimensional open framework structures composed of Ln-chains and dianthracence linkages. Within the chain, the dimers of {Ln2 O2 (OPO)2 } are connected by oxalate anions. The MOFs generate channels along the a -axis which are hydrophilic lined with protonated phosphonate moieties, and hence exhibit high affinity towards adsorption of water and ammonia. Thermogravimetric analysis and differential scanning calorimetry (DSC) measurements revealed that MDAF-4Ln experienced two consecutive phase transitions: first, the loss of all lattice and coordinated water molecules and then, the dissociation of amp2 H2 2− . Detailed studies on MDAF-4Dy demonstrated that the thermo-induced structural transformations were accompanied by significant changes in its single-molecule magnetic behavior and luminescence properties.